Unleashing the healing potential: Exploring next-generation regenerative protein nanoscaffolds for burn wound recovery - Liangwei Si; Xiong Guo; Hriday Bera; Yang Chen; Fangfang Xiu; Peixin Liu; Chunwei Zhao; Yasir Faraz Abbasi; Xing Tang; Vito Foderà; Dongmei Cun; Mingshi Yang (Elsevier, 2023)
Burn injury is a serious public health problem and scientists are continuously aiming to develop promising biomimetic dressings for effective burn wound management. In this study, a greater efficacy in burn wound healing and the associated mechanisms of α-lactalbumin (ALA) based electrospun nanofibrous scaffolds (ENs) as compared to other regenerative protein scaffolds were established. Bovine serum albumin (BSA), collagen type I (COL), lysozyme (LZM) and ALA were separately blended with poly(ε-caprolactone) (PCL) to fabricate four different composite ENs (LZM/PCL, BSA/PCL, COL/PCL and ALA/PCL ENs). The hydrophilic composite scaffolds exhibited an enhanced wettability and variable mechanical properties. The ALA/PCL ENs demonstrated higher levels of fibroblast proliferation and adhesion than the other composite ENs. As compared to PCL ENs and other composite scaffolds, the ALA/PCL ENs also promoted a better maturity of the regenerative skin tissues and showed a comparable wound healing effect to Collagen spongeⓇ on third-degree burn model. The enhanced wound healing activity of ALA/PCL ENs compared to other ENs could be attributed to their ability to promote serotonin production at wound sites. Collectively, this investigation demonstrated that ALA is a unique protein with a greater potential for burn wound healing as compared to other regenerative proteins when loaded in the nanofibrous scaffolds.